2010
DOI: 10.1097/mbc.0b013e3283333c7c
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and childhood right atrial thrombosis: recognition and a risk-stratified treatment approach

Abstract: Pediatric literature and guidelines of treatment options for right atrial thrombosis (RAT) are lacking; thus, this review summarizes the available literature on RAT in infants and children. Medline search identified 35 publications, with 27 prospective or retrospective case series included for data analysis. A total of 122 cases of RAT were identified. The mean age of patients is 3.58 years (n = 86) with a strong predominance in the neonatal and infancy period. Ninety-one percent of cases were found to be asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 42 publications
3
40
1
1
Order By: Relevance
“…[261][262][263][264][265][266][267][268][269][270][271][272][273] There are no specifi c guidelines for the use of thrombectomy in children, but there is general consensus that the TE recurrence rate and risk of long-term vas-tive of whether the infant received no therapy, UFH, or LMWH, with ‫ف‬ 70% of affected kidneys having irreversible renal atrophy. 279 Approximately 20% of children had hypertension on long-term follow-up, and 3% of children developed chronic renal failure.…”
Section: Surgical Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…[261][262][263][264][265][266][267][268][269][270][271][272][273] There are no specifi c guidelines for the use of thrombectomy in children, but there is general consensus that the TE recurrence rate and risk of long-term vas-tive of whether the infant received no therapy, UFH, or LMWH, with ‫ف‬ 70% of affected kidneys having irreversible renal atrophy. 279 Approximately 20% of children had hypertension on long-term follow-up, and 3% of children developed chronic renal failure.…”
Section: Surgical Therapymentioning
confidence: 99%
“…273,520 The epidemiology and risk associated with right atrial thrombosis appears to be different in children compared with adults. 273 The natural history appears to be resolution irrespective of therapy, and many children are asymptomatic. Risk stratifi cation based on clot size and mobility appears to be useful.…”
Section: Children With Right Atrial Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, screening for underlying causes of cryptogenic stroke with ultrasound of the lower extremities revealed venous thrombosis The most probable releasing factor (and causative) of this event was a few days previously reported, sport's related, minor lower extremity injury, a relationship supported by literature. [36].…”
Section: Deep Venous Thrombosis and Cryptogenic Strokementioning
confidence: 99%
“…In the incident of right atrial thrombus, different treatment modalities are reported such as surgical thrombectomy, thrombolysis, anticoagulation therapy or observation only, the choice of which depended mainly on underlying etiology [36].…”
Section: Treatment Guidelinesmentioning
confidence: 99%